Cinética de bioacumulação do íon Pb+² na macrófita aquática Pistia stratiotes - Costa Junior, Ismael Laurindo (2007)
In the present work the lead uptake onto a living free floating aquatic macrophyte Pistia stratiotes was investigated. The bioaccumulation mechanism were applied to understand the metal uptake by the autochthonous free floating Pistia, common in ponds and shallow lakes from southern Brazilian states from a hydroponics solution. The experiment was performed using several healthy acclimatized plants Pistia Stratiotes. For the metal uptake, aquatic plants were grown in plastic containers containing 5 L test liquids and 2 mg L-1 of into a greenhouse for 35 days. Twenty one replicates were used for metal treatment. Only healthy acclimatized plants of a uniform size and weight were selected for experimental purposes. Approximately 30 g wet weights of Pistia stratiotes were put into aqueous solution. The room temperature and pH were daily measured and deionized water was adding to compensate for water losses. Seven collections were carried out during five weeks which both plants and test liquids were collected from three replicate containers of each metal treatment. The plant wet weight was measured before the experiment and after the each collection. Plants were oven-dried at 80°C for 72 hours and weighted reducing their mass around 94 %, and then they were grinded and digested by acid attack. A Gallium internal standard was added to an aliquot of water or digested plant. An aliquot of 5µL was deposited on a pre-cleaned acrylic disk (ø30 mm, 3 mm thick) and dried at room temperature. Blank control samples containing de-ionized water and all reagents used in the experiment were prepared by the same procedure. Metal concentrations on dried weight plants and cultivation water were measured using the SR-TXRF. The data from the lead bioaccumulation experiment using living Pistia stratiotes have been represented by the irreversible Langmuir, reversible Langmuir, first order and second order models. The maximum capacity of lead removal (qmax ) and the kinetic constant of lead bioaccumulation (k) were the adjustable parameters. The model that described in more appropriate way the bioacumulação was of the kinetic of the reversible Langmuir, presenting a qmax of 0,21 mg g-1 and k of 0,69 L mg-1 d-1, what it demonstrates a good removal of Pb+2 to the long one of the time.